Diagnostic quality and scoring of synovitis, tenosynovitis and erosions in low-field MRI of patients with rheumatoid arthritis: a comparison with conventional MRI. Issue 4 (26th October 2006) - Schirmer, Claudia; Scheel, Alexander K; Althoff, Christian E; Schink, Tania; Eshed, Iris; Lembcke, Alexander; Burmester, Gerd-Rüdiger; Backhaus, Marina; Hamm, Bernd; Hermann, Kay-Geert A
Abstract : Objective: To compare dedicated low-field MRI (lfMRI) with conventional MRI (cMRI) in the detection and scoring of synovitis, tenosynovitis and erosions in patients with rheumatoid arthritis. Patients and methods: The wrist and finger joints of 17 patients with rheumatoid arthritis (median (range) disease duration 8 years (7–12); Disease Activity Score 3.3 (2.6–4.5)) were examined by 0.2 T lfMRI and 1.5 TcMRI. The protocols comprised coronal spin-echo and three-dimensional gradient-echo sequences before and after contrast medium administration. Synovitis of the metacarpophalangeal and proximal interphalangeal joints 2–5 and the wrist joints was scored according to Outcome Measures in Rheumatology recommendations. Tenosynovitis and erosions were scored using 4-point and 6-point scales, respectively. The results were analysed by calculating κ values and performing McNemar's test intra-individually on a joint-by-joint basis. Results: Agreement between the two MRI techniques was good to excellent for synovitis and erosions, and moderate for tenosynovitis. Of the 306 joints evaluated, 245 and 200 joints showed synovitis in lfMRI and cMRI, respectively. Scoring of synovitis of the finger joints yielded κ values from 0.69 to 0.94. Of the 68 flexor tendons evaluated, tenosynovitis was diagnosed by lfMRI in 24 and by cMRI in 33 instances. Of the 391 bones evaluated, 154 and 139 showed erosions in lfMRI and cMRI, respectively. κ values for erosion scores were between 0.65 and 1. Conclusion: Dedicated, lfMRI shows high agreement with cMRI in diagnosing and scoring synovitis, tenosynovitis and erosions in rheumatoid arthritis when using standardised scoring systems.